PROTECTION OF VICTIMS OF GENDER-BASED VIOLENCE - Phrianindya Ayu Setyaningsih; Lidia Rina Dyahtaryani; Sudarto Rahmat (JILPR Journal Indonesia Law and Policy Review, 2026)
This research examines the protection of victims of gender-based violence under Law Number 12 of 2022 concerning the Crime of Sexual Violence (UU TPKS). Gender-based violence constitutes a serious violation of human rights that causes significant physical, psychological, social, and economic impacts on victims. Although the Indonesian government has enacted the TPKS Law as a legal framework to address sexual violence, the implementation of victim protection still encounters various challenges within the criminal justice system. The objectives of this research are to analyze the concept of victim protection for gender-based violence under the TPKS Law and to examine the obstacles in determining victim protection as well as their implications for the fulfillment of victims' rights. This research employs a normative legal research method using a statutory approach and a conceptual approach. The analysis is conducted using victimology theory, punishment theory, and criminal justice system theory. The results of this study indicate that the TPKS Law provides a more comprehensive legal framework for victim protection through the recognition of victims' rights to handling, protection, and recovery, including the right to restitution and integrated recovery services. However, the implementation of victim protection still faces several obstacles, including the limited availability of implementing regulations, lack of victim-oriented perspectives among law enforcement officers, inadequate victim recovery facilities, and persistent social stigma and victim blaming within society. Therefore, strengthening the implementation of the TPKS Law through improved capacity of law enforcement officials, enhancement of victim protection services, and transformation of societal perspectives is essential to ensure effective protection for victims of gender-based violence.